Linguistic Relativity in SLA: Toward a New Research Program. Issue 4 (15th October 2014) - Bylund, Emanuel; Athanasopoulos, Panos
<x xml:space="preserve">Abstract</x> The purpose of the current article is to support the investigation of linguistic relativity in second language acquisition and sketch methodological and theoretical prerequisites toward developing the domain into a full research program. We identify and discuss three theoretical‐methodological components that we believe are needed to succeed in this enterprise. First, we highlight the importance of using nonverbal methods to study linguistic relativity effects in second language (L2) speakers. The use of nonverbal tasks is necessary in order to avoid the circularity that arises when inferences about nonverbal behavior are made on the basis of verbal evidence alone. Second, we identify and delineate the likely cognitive mechanisms underpinning cognitive restructuring in L2 speakers by introducing the theoretical framework of associative learning. By doing so, we demonstrate that the extent and nature of cognitive restructuring in L2 speakers is essentially a function of variation in individual learners' trajectories. Third, we offer an in‐depth discussion of the factors (e.g., L2 proficiency and L2 use) that characterize those trajectories, anchoring them to the framework of associative learning, and reinterpreting their relative strength in predicting L2 speaker cognition.